In Operando X‐Ray Nanodiffraction Reveals Electrically Induced Bending and Lattice Contraction in a Single Nanowire Device. Issue 9 (21st December 2015) - Wallentin, Jesper; Osterhoff, Markus; Salditt, Tim
Abstract : Hard X‐ray diffraction (XRD) using a nanofocused beam is used to measure both lattice contraction and bending in a single nanowire device under electric bias. The shape of the nanowire is reconstructed in 3D with sub‐nanometer precision. As the bias voltage is gradually increased, nonreversible structural changes in the contact regions are observed, correlated with degradation of the electrical conductance.